Propagator, tree-level unitarity and effective nonrelativistic potential for higher-derivative gravity theories in D dimensions - Accioly, A.; Azeredo, A.; Mukai, H. (American Institute of Physics (AIP), 2002)
A prescription for computing the propagator for D-dimensional higher-derivative gravity theories, based on the Barnes-Rivers operators, is presented. A systematic study of the tree-level unitarity of these theories is developed and the agreement of their linearized versions with Newton's law is investigated by computing the corresponding effective nonrelativistic potential. Three-dimensional quadratic gravity with a gravitational Chern-Simons term is also analyzed. A discussion on the issue of light bending within the framework of both D-dimensional quadratic gravity and three-dimensional quadratic gravity with a Chern-Simons term is provided as well. (C) 2002 American Institute of Physics.